Early Fusion Status after Posterior Lumbar Interbody Fusion with Cortical Bone Trajectory Screw Fixation: A Comparison of Titanium-Coated Polyetheretherketone Cages and Carbon Polyetheretherketone Cages - Hironobu Sakaura; Atsunori Ohnishi; Akira Yamagishi; Tetsuo Ohwada (Asian Spine Journal, 2019)
Study Design Retrospective cohort study. Purpose We recently reported that when compared to posterior lumbar interbody fusion (PLIF) using traditional pedicle screw fixation, PLIF with cortical bone trajectory screw fixation (CBT-PLIF) provided favorable clinical outcomes and reduced the incidence of symptomatic adjacent segment pathology, but resulted in relatively lower fusion rates. Since titanium-coated polyetheretherketone (PEEK) cages (TP) could improve and accelerate fusion status after CBT-PLIF, early fusion status was compared between CBT-PLIF using TP and carbon PEEK cages (CP). Overview of Literature A systematic review demonstrated that clinical studies at this early stage show similar fusion rates for TP compared to PEEK cages. Methods We studied 36 consecutive patients undergoing CBT-PLIF with TP (TP group) and 92 undergoing CBT-PLIF with CP (CP group). On multiplanar reconstruction computed tomography (MPR-CT) at 6 months postoperatively, vertebral endplate cysts (cyst signs) were evaluated and classified as diffuse or local cysts. Early fusion status was assessed by dynamic plain radiographs and MPR-CT at 1 year postoperatively. Results The incidences of cyst signs, diffuse cysts, and early fusion rate in the TP and CP groups were 38.9% and 66.3% (p<0.01), 16.7% and 32.6% (p=0.07), and 83.3% and 79.3% (p>0.05), respectively. Combining the two groups, 22 of 36 patients with diffuse cysts had nonunion at 1-year follow-up, compared to only three of 92 patients with local cysts or without cyst signs (p<0.01). Conclusions Despite having fewer patients with endplate cysts at 6 months (a known risk factor for nonunion), the TP group had the same fusion rate as the CP group at 1-year follow-up. Thus, TP did not accelerate the fusion process after CBT-PLIF.